Analisis Konflik Batin dalam Film Penyalin Cahaya Sutradara Wregas Bhanuteja - Elmustian, Elmustian; Charlina, Charlina; Melani, Endah (Jurnal Ilmiah Global Education, 2025)
This research is a type of qualitative descriptive research. The purpose of this research is to describe Kurt Lewin's inner conflict of approaching, moving away, approaching and moving away. Based on the results of the research "Analysis of Inner Conflict in the Film Pecopylin Cahaya Sutrada Wregas Bhanuteja", the author found 43 forms of inner conflict and 43 conflict resolutions for Suryani characters. The conflicts consisted of 3 approaching-approaching conflicts, 11 approaching-away conflicts, and 31 approaching-away conflicts. From these results, approach-away conflict was the most dominant type of conflict with 31 conflicts experienced by Suryani. This reflects the complexity of the emotions and situations that Suryani faces as a victim of sexual harassment in her efforts to seek justice amidst social and cultural pressure. Conflict resolution consists of 5 positive valences, 32 negative valences, and 6 neutral valences. The many negative valences found in the Syriac conflict resolution illustrate the difficult and challenging reality for victims of sexual violence. This situation reflects the social pressure, distrust and stigma faced by victims, so that many decisions they make result in negative consequences, both emotional and social.